Le rôle du co-texte dans l’antonymie adjectivale - Perz, Magdalena (Neophilologica, 2017)
This paper discusses the interpretation of antonymous adjectives. The example of the French adjective frais, analyzed in the paper on the basis of the object oriented approach, allows the Author to demonstrate that context is found to be highly discriminable in choosing an antonymic partner. A co-textual approach can overcome the inadequacies of classical dictionaries in the organization of the lexical structure of a language.